A CHILD WITH TETRALOGY OF FALLOT PRESENTING WITH COMPLICATIONS OF INFECTIVE ENDOCARDITIS, CEREBRAL ABSCESS, AND UNDERNUTRITION - Yasmin, AA Ayu Dwi Adelia; Gunawijaya, Eka (Medicina; Vol 46 No 1 (2015): Januari 2015, 2015)
Tetralogy of Fallot  (TOF)  is a congenital heart disease  that consists of  four anatomical anomalies,namely ventricular septal defect, pulmonary stenosis or obstruction of the right ventricular outflowtract, right ventricular hypertrophy, and overriding aorta. Tetralogy of Fallot is frequently associatedwith complications that could affect morbidity and mortality because of its complex cardiac lesions.Good understanding of the natural history and complications of this disease is very important to guidethe management of patients. We reported a 4-year old girl with classic TOF with complications ofinfective  endocarditis,  cerebral  abscess,  and undernutrition. Despite  optimal medical  therapy,  thepatient?s condition showed no satisfying improvement. Since the parents were refused to take moreaggressive measure by undergoing surgical therapy, so that patient care remains focused on supportiveand palliative aspects. [MEDICINA 2015;46:37-41]. Tetralogy of Fallot (TOF) merupakan suatu penyakit jantung kongenital yang terdiri dari empat anomalianatomis, antara lain ventricular septal defect, pulmonary stenosis atau obstruksi pada right ventricleoutflow tract, hipertrofi ventrikel kanan, dan overriding aorta. Tetralogy of Fallot sering disertai denganberbagai  komplikasi  yang  dapat mempengaruhi morbiditas  dan mortalitas  karena  kelainan  inimerupakan kelainan kongenital kardiak yang kompleks. Pemahaman yang baik mengenai perjalananalamiah  dan komplikasi  penyakit  ini  sangat  penting untuk mengetahui  penatalaksanaan  pasien.Kami melaporkan seorang anak perempuan berusia 4 tahun dengan TOF klasik yang juga menderitakomplikasi endocarditis infektif, abses serebral, dan gizi kurang. Walaupun telah memperoleh terapimedikamentosa  yang  optimal,  kondisi  pasien  tidak menunjukkan  perbaikan  yang memuaskan.Orangtua  pasien  telah menolak  pemberian  tindakan  yang  lebih  agresif,  yaitu  dengan  terapipembedahan,  oleh  karena  itu  penatalaksanaan  pasien  lebih  difokuskan  pada  aspek  suportif  danpaliatif. [MEDICINA 2015;46:37-41].
Keywords: tetralogy of Fallot, infective endocarditis, brain abscess, undernutrition